Capturing Emerging Realities in Citizen Engagement in Science in Social Media: A Social Media Analytics Protocol for the Allinteract Study - Cristina M. Pulido Rodriguez (SAGE Publishing, 2021)
In the digital era, social media has become a space for the socialization and interaction of citizens, who are using social networks to express themselves and to discuss scientific advances with citizens from all over the world. Researchers are aware of this reality and are increasingly using social media as a source of data to explore citizens’ voices. In this context, the methods followed by researchers are mainly based on the content analysis using manual, automated or combined tools. The aim of this article is to share a protocol for Social Media Analytics that includes a Communicative Content Analysis (CCA). This protocol has been designed for the Horizon 2020 project Allinteract, and it includes the social impact in social media methodology. The novel contribution of this protocol is the detailed elaboration of methods and procedures to capture emerging realities in citizen engagement in science in social media using a Communicative Content Analysis (CCA) based on the contributions of Communicative Methodology (CM).